The effectiveness of celebrity endorsements: a meta-analysis - Knoll, Johannes; Matthes, Jörg (Journal of the Academy of Marketing Science, 2017)
Celebrities frequently endorse products, brands, political candidates, or health campaigns. We investigated the effectiveness of such endorsements by meta-analyzing 46 studies published until April 2016 involving 10,357 participants. Applying multilevel meta-analysis, we analyzed celebrity endorsements in the context of for-profit and non-profit marketing. Findings revealed strong positive and negative effects when theoretically relevant moderators were included in the analysis. The most positive attitudinal effect appeared for male actors who match well with an implicitly endorsed object (d = .90). The most negative effect was found for female models not matching well with an explicitly endorsed object (d = −.96). Furthermore, celebrity endorsements performed worse compared to endorsements of quality seals, awards, or endorser brands. No publication bias was detected. The study has theoretical and practical implications, and provides an agenda for future research.